I survived the attacks of September 11, 2001 - Tarshis, Lauren; Egbert, Corey (New York Scholastic Inc., 2021)
"A gripping graphic novel adaptation of Lauren Tarshis's bestselling I Survived the Attacks of September 11, 2001, in time for the 20th anniversary of 9/11. The only thing Lucas loves more than football is his Uncle Benny, his dad's best friend at the fire department where they both work. Benny taught Lucas everything about football. So when Lucas's parents decide the sport is too dangerous and he needs to quit, Lucas has to talk to his biggest fan. The next morning, Lucas takes the train to the city instead of the bus to school. It's a bright, beautiful day in New York. But just as Lucas arrives at his uncle's firehouse, everything changes -- and nothing will ever be the same again. Lauren Tarshis's New York Times bestselling I Survived series comes to vivid life in bold graphic novels. Perfect for readers who prefer the graphic novel format, or for existing fans of the I Survived chapter book series, these graphic novels combine historical facts with high-action storytelling that's sure to keep any reader turning the pages. Includes a nonfiction section at the back with facts and photos about the real-life event"--
Ages 8-12
Grades 4-6